From the History of the Georgian Integral Nationalism (“The Fascist Movement of Georgia”) - Matsaberidze, Malkhaz (Politics / პოლიტიკა; 2020: მეორე ნომერი, 2020)
The paper analyzes the ideology of the political union “Fascist Movement of Georgia,” which existed among the emigrant communities of Georgia, through reflecting the publications and party program appearing in the journal “Khartlosi” in 1937-1939. This ideology could be considered as a kind of integral nationalism. The group of the Georgian emigrants (Sh.Maglakelidze, V.Nozadze, K.Salia, N.Dadiani, etc) tried to find a concrete way for the liberation of Georgia on the basis of the fascism, which was considered as a successful ideology and party program by them in the second half of the 1930s. They argued that the Georgian version of the fascism will unite the nation, oppose the communist regime and with the support of the fascist states will bring freedom to Georgia. During its 3 years-long existence, the “Fascist Movement of Georgia” remained as the theoretical union and it had never cooperated neither with Italian fascists, nor with the German Nazists. In 1939, after the signature of the Molotov–Ribbentrop Pact, the publication of the journal “Kartlosi” was stopped and the “Fascist Movement of Georgia” was dissolved. The failure of the fascist regimes and the belie of their criminal activities contributed to the discreditation and decry of the fascist ideology. Correspondingly, this form of the Georgian integral nationalism was not further developed. Those persons, which were united in the “Fascist Movement of Georgia” were the patriots and famous public figures of Georgia.
Keywords: Georgia, Georgian Emigration, Integral Nationalism, Fascism, Fascist Movement of Georgia